Penentuan Jarak Terpendek Menggunakan Metode Dijkstra Pada Data Spasial Openstreetmap (Studi Kasus : Pada Perusahaan Pengantaran Barang Wahana Logistik Kota Malang) - Muhammad Ashari Fajar Nugroho; Yan Watequlis Syaifudin; Dwi Puspitasari (LPPM UBHINUS MALANG, 2019)
Openstreetmap is a web-based project to create a free and open worldwide map, built entirely by volunteers by conducting surveys using gps, digitizing satellite imagery and collecting and freeing available geographic data in the public. Many types of digital maps are available on the internet, but most have legality limitations. This makes the user unable to use the map freely. And also on openstreetmap still does not support to search the track with data input of more than 1 destination. Wahana Logistics is one of the logistics shipping services in Malang. But in openstreetmap, the location of the Wahana logistics is still not available at all. Therefore, a system for determining the shortest pathway was made using the Dijkstra algorithm at a Wahana Logistics case study. The system is in the form of a web using a codeigniter framework, with the consideration that the web can be accessed by all members of Wahana Logistics without differentiating platform used by user. The dijkstra is one of methods to determine shortest path, but before entering method calculation, path data will be processed using haversine formula to determine the distance between the node s. To process a path search, this system provides search facility with multiple input purpose. So, the resulting paths according with data entered by user